Intradermal delivery of SARS-CoV-2 RBD3-Fc mRNA vaccines via a needle-free injection system induces robust immune responses in rats - Wang, Cenrong; Tang, Xin; Jiang, Chenghan; Zhang, Yu; Han, Bo; Sun, Yi; Guo, Jianfeng; Peng, Hanyu; Wang, Zihan; Wang, Yipeng; Zhang, Jialu; Zhang, Yong; et al. (Frontiers in Immunology, 2025)
IntroductionNeedle-free injection system (NFIS) is easy to operate and can decrease needle phobia. Besides, NFIS can increase the interaction of antigens in a more dispersed manner with immune cell at local injection site, which may improve the immune responses of mRNA vaccines. Although SARS-CoV-2 mRNA vaccines have great success, universal vaccines are urgently needed. Delivering universal mRNA vaccines by NFIS is preferred to combat COVID-19.MethodsRBD3-Fc mRNA expressing BA.4, Delta, and prototype RBD, and human IgG Fc with YTE mutation was designed and synthesized. The safety and immune responses of universal RBD3-Fc naked mRNA and mRNA-LNP vaccines delivered intradermally using NFIS (named GV-01) and intramuscularly via needles were evaluated and compared in rats.ResultsThe prime-boost regimen administered by two routes resulted in potent immune responses and intradermal delivery displays comparable or better performance in terms of binding antibodies, neutralizing antibodies and T cell responses. Naked mRNA vaccines were functional, but less effective than mRNA-LNP vaccines.DiscussionThe above results suggest that RBD3-Fc vaccines are safe and immunogenic and NFIS can be used as an alternative to needles/syringes for the inoculation of mRNA-LNP vaccines to elicit robust systematic immune responses.